Uji Penggunaan Bacillus sp. sebagai Kandidat Probiotik Untuk Pemeliharaan Rajungan (Portunus sp.) - Linggarjati, Kharisma Firdaus; Djunaedi, Ali; Subagiyo, Subagiyo (977-2407769)
Blue crab is one of the economically marine commodities and have high potential export. During this blue crab requirement derived from nature catches because in blue crab aquaculture not yet good branch out. To low survival rate of blue crab caused by bacterium vibrio disease, in addition to the content of nitrogen and phosphate can also affect the blue crab medium. This research as a purpose to test the effect of probiotic bacillus aplication to water quality and the total number of bacteria in the blue crab medium. the research was conducted with 2 stages, that is isolation and selection bacillus bacteria stages as probiotic and testing phase the effect of probiotic bacillus on water quality and the total number of bacteria. The result showed that probiotic bacillus with density 106 cfu/ml to reduce the content of ammonia (NH3), nitrite (NO2) and the total number of bacteria. While probiotics with density 105 cfu/ml to reduce the total number of bacteria in the blue crab medium, but have not been able to reduce the content of ammonia (NH3) and nitrite (NO2).